2019
DOI: 10.3390/ijerph16214192
|View full text |Cite
|
Sign up to set email alerts
|

Emotion, Psychological Well-Being and Their Influence on Resilience. A Study with Semi-Professional Athletes

Abstract: The objective of the present study is to analyze the influence of coaches on emotional intelligence and on levels of anxiety, motivation, self-esteem, and resilience among athletes. Five-hundred forty-seven semi-professional athletes between the ages of 16 and 19 participated in this study. Various statistical analyses were conducted which explain the causal relationships between the variables. The results, obtained using a structural equations model, find that while autonomy support positively predicts emotio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 52 publications
0
15
0
4
Order By: Relevance
“…More recently, Ammar et al ( 2020a ) have also reported an increased number of people to have experienced negative effects on mental wellbeing and emotional status (10–16.5%, small to moderate change) as a result of home confinement. Such negative states may be induced by nervousness, preoccupation and apprehension caused by an individual's perception of the situation (Trigueros et al, 2019 ). This is likely related to the current COVID-19 pandemic, as athletes experience uncertainty about their return to competition and their performance level (Andreato et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Ammar et al ( 2020a ) have also reported an increased number of people to have experienced negative effects on mental wellbeing and emotional status (10–16.5%, small to moderate change) as a result of home confinement. Such negative states may be induced by nervousness, preoccupation and apprehension caused by an individual's perception of the situation (Trigueros et al, 2019 ). This is likely related to the current COVID-19 pandemic, as athletes experience uncertainty about their return to competition and their performance level (Andreato et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The main limitation is the linearity of the model, that is, in a single event it is the one that opposes the individual [21]. In addition, it does not take into account the protective role that emotions play in the behavior of individuals [22] and as facilitators when dealing with the problem [23]. Fletcher and Sarkar [24] reconceptualized the definition of resilience due to the limitations presented by the meta-theory.…”
Section: Resilencementioning
confidence: 99%
“…In a conjunctive moderation study with 218 student-athletes, Lu et al found that coaches' social support fosters athletes' resilience to prevent stress-induced burnout in athletes [42]. A study with 547 semi-professional athletes aged 16-19 years analyzed the influence of coaches on emotional intelligence and on levels of anxiety, motivation, self-esteem, and resilience [43]. Trigueros et al found self-esteem to positively predict self-determined motivation, however, anxiety had a negative effect on it.…”
Section: Athlete Psychological Resiliencementioning
confidence: 99%
“…The social aspects of being an adolescent -young adult athlete, especially with regards to the relationship with the coach, were proposed in preliminary empirical evidence of the psychological construct of interrelations during competition and the effect upon athlete psychological well-being. Trigueros et al found the need for further studies to confirm that self-determined motivation positively predicts athlete resilience [43].…”
Section: Athlete Psychological Resiliencementioning
confidence: 99%